Disorders of the hemostasis system while doing coronary shunting on a working heart - A. P. Mazur; P. V. Gurin; M. M. Babich (Клінічна хірургія, 2019)
Objective. To investigate the connection between application of solutions for infusion and parameters of the hemostasis system while the elective operations performance of coronary shunting on the working heart.